Optics Visualization Web-Based as A Physics Learning Media in Senior High School - Khusnul, Faprilia; Nasir, Muhammad; Azhar, Azhar (Journal of Educational Sciences, 2022)
The laboratory has an important role in the learning of physics. The experimental characteristics and abstract concepts of physics that cause difficulties in the physics learning process. Tools and materials are limited often used as an problem in the practicum activities. This study aims to develop a learning  media of optics visualization based website as an alternative the limited of laboratory tools. This research includes research and development with ADDIE model (Analysis, Design, Development, Implementation and Evaluate). To collect the data, instrument are used to analyze such as a validation questionnaire. The data analysis were used the Aiken,s V formula. Based on the results of the validity test by experts, the optics visualization learning media web-based was declared valid with an average rating of 0.87 on the design aspect, 0.89 on the pedagogic aspect, 0.88 on the content aspect and 0.84 on the technical aspect. Thus the optics visualization learning media web-based developed has been declared valid and can be used as a media of learning in teaching and learning activities in class.